2022
DOI: 10.1136/bmjopen-2022-060754
|View full text |Cite
|
Sign up to set email alerts
|

Patient-related factors associated with superficial surgical site infection and progression to a periprosthetic joint infection after elective primary total joint arthroplasty: a single-centre, retrospective study in Sweden

Abstract: ObjectivesSuperficial surgical site infection (SSSI) may increase the risk of serious complications such as periprosthetic joint infection (PJI). This study aims to identify patient-related risk factors associated with SSSI and investigate their correlation with the progression of PJI.DesignIn this retrospective study, 1191 elective hip and knee prostheses were included. Patients were interviewed 3–5 months after surgery to answer questions about the postoperative period. Patient records were reviewed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Superficial SSI occurred in 8%, which is higher than the 1% to 2.5% reported from the USA (29) but similar to the 7% in Sweden (1). We identified an association with elevated BMI and HbA1c.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Superficial SSI occurred in 8%, which is higher than the 1% to 2.5% reported from the USA (29) but similar to the 7% in Sweden (1). We identified an association with elevated BMI and HbA1c.…”
Section: Discussionsupporting
confidence: 62%
“…Superficial SSI progressed to PJI in 7 of 57 (12%) cases, which is lower than in a recent report from Sweden where the progression rate was 29%. However, their follow-up time was slightly longer than was used in our study (1).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…SSI defined as an infection that occurs at or near the surgical incision site within 30 days of surgery can have serious consequences, including prolonged hospital stays, repeat surgery, prolonged morbidity and even death 13,14 . Previous studies have shown that the occurrence of SSI after orthopaedic‐related surgery is a multifactorial event influenced by a variety of factors 15,16 . Although there is a large body of literature on the subject, it often leads to inconsistent conclusions and a lack of consensus in identifying these risk factors 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 Previous studies have shown that the occurrence of SSI after orthopaedic‐related surgery is a multifactorial event influenced by a variety of factors. 15 , 16 Although there is a large body of literature on the subject, it often leads to inconsistent conclusions and a lack of consensus in identifying these risk factors. 17 , 18 This discrepancy in the literature suggests an urgent need for more comprehensive studies.…”
Section: Introductionmentioning
confidence: 99%